Prediction Score for Cervical Spine Fracture in Patients with Traumatic Neck Injury - Natsinee Athinartrattanapong; Chaiyaporn Yuksen; Sittichok Leela-amornsin; Chetsadakon Jenpanitpong; Sirote Wongwaisayawan; Pittavat Leelapattana (Neurology Research International)
Background. Cervical spine fracture is approximately 2%–5%. Diagnostic imaging in developing countries has several limitations. A computed tomography scan is not available 24 hours and not cost-effective. This study aims to develop a clinical tool to identify patients who must undergo a computed tomography scan to evaluate cervical spine fracture in a noncomputed tomography scan available hospital. Methods. The study was a diagnostic prediction rule. A retrospective cross-sectional study was conducted between August 1, 2016, and December 31, 2018, at the emergency department. This study included all patients aged over 16 years who had suspected cervical spine injury and underwent a computed tomography scan at the emergency department. The predictive model and prediction scores were developed via multivariable logistic regression analysis. Results. 375 patients met the criteria. 29 (7.73%) presented with cervical spine fracture on computed tomography scan and 346 did not. Five independent factors (i.e., high-risk mechanism of injury, paraparesis, paresthesia, limited range of motion of the neck, and associated chest or facial injury) were considered good predictors of C-spine fracture. The clinical prediction score for C-spine fracture was developed by dividing the patients into three probability groups (low, 0; moderate, 1–5; and high, 6–11), and the accuracy was 82.52%. In patients with a score of 1–5, the positive likelihood ratio for C-spine fracture was 1.46. Meanwhile, those with a score of 6–11 had an LR+ of 7.16. Conclusion. In a noncomputed tomography scan available hospital, traumatic spine injuries patients with a clinical prediction score ≥1 were associated with cervical spine fracture and should undergo computed tomography scan to evaluate C-spine fracture.